Full frontal facelift a comparative study on the modernization of layout and design of Philippine national broadsheets - Imperial, Ian Vincent Villa Juan (2012)
"This thesis aims to uncover the reasons behind the slow modernization of newspaper layout and design of Philippine national broadsheets by comparing the most and the least "modern" front page designs, which were based from the rankings given by the focus group discussion with visual communication students, and the analysis made by the researchers. Interviews with their respective art directors provided deeper insights on design modernization, that economic factors play a major role in laying out and designing newspapers despite their indirect relationship with one another. We could then conclude that the print news industry is alive given that these economic factors are also the determinants to the life and death of a newspaper."